Upaya Pastry Section Menjaga Kualitas Produk Bakery Di Hotel Eastparc Yogyakarta - Nur Raga Ardhani; Ani Wijayanti - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2016)
Yogyakarta city as a cultural and educational city become a very interest tourism destination of many tourist. The tourism growth in Yogyakarta have reached high level in 2012, 39,95%. The high interest of touris visit have provided opportunity in tourism industry, one of them is business accomodation services. The number of accomodation in Yogyakarta until 2014 is registered as much as 417 hotels, consist of 54 star hotels and 363 non-star hotels. Eastparc hotel is one of five star hotel in Yogyakarta that provide accommodation and food-beverage services. Eastparc hotel manage their own pastry as one of effort in maintaining and increasing service quality in food and beverage, particularly bakery product. The research design is descriptive qualitative research wich take place at pastry section in Eastparc hotel Yogyakarta. The research result state that pastry section implementated three operational standard, there are storing standard, tool using standard, and employee operational standard. Pastry section produce many kind of bakery are Cake. Pie, Cookies, Soft roll bread., Multimalt bread, Rye bread., Hard roll, Praztel bread, Sweet bread, Toast, Croissant, and Danish. However, there are obstacles faced by pastry section related with raw material, product storing, and employee competencies. Three main points able to implement to overcome the obstacles are cooperation with other departement, improve employee competencies, and quality control.. Key Words : Hotel, Pastry, Quality, Bakery, Operational Standard